(untitled) (Orfeu, 2024)
This ethnomusicological study investigates the practice of Fandango Caiçara in Itapoá, Santa Catarina, highlighting the substitution of the traditional ten-string brazilian guitar called "viola caiçara" with the regular guitar in the region. The research includes musical analyses based on phonographic records and two field trips, revealing similarities in strumming techniques, poetry, and improvisation with other areas where Fandango Caiçara is practiced. A pivotal aspect is the tuning of the guitar, challenging the previous proposal of the Rio Abaixo tuning in A Major; the findings suggest that the Pelas Três tuning may be more suitable in Itapoá. The study underscores the significance of incorporating the northern coast of Santa Catarina into the territory of Fandango Caiçara, officially recognized as Intangible Cultural Heritage of Brazil. Furthermore, it identifies avenues for future research, such as investigating the guitar tuning in the Folia do Divino Espírito Santo in Guaratuba, Paraná, and exploring Caiçara culture in other municipalities along the Baía da Babitonga, Santa Catarina.